Attention: Implied Volatility Spreads and Stock Returns. Issue 4 (1st October 2020) - Gao, Xuechen; (Wesley) Wang, Xuewu; Yan, Zhipeng
Abstract: Using a new and direct measure of investor attention generated from the SEC's EDGAR log files, we revisit the stock return predictability of call-put implied volatility spread through the lens of investor attention. We find that as investor attention heightens, the volatility spread return predictability becomes more pronounced, providing favorable evidence for the informed trading hypothesis as opposed to the mispricing hypothesis. More importantly, we document the construction and profitability of spread-and-high-attention portfolios. A portfolio that goes long on stocks with the highest investor attention and the highest volatility spread and short on stocks with the highest attention and the lowest volatility spread generates a Fama-French 5-factor monthly alpha of 2.43%.